Role of Physical activity in abating Non-Communicable Diseases: A survey of residents of Central Park Housing Society, Lahore - Shehnaz Khan; Mehrunisa Hassan; Mamoona Shafique; Saira Farhat; Saba Iftkhar; Shamim Akhter (University of Lahore, 2024)
Objective: Regular physical activity is beneficial to both physical and emotional well-being. The present study goal is to observe how lack of physical exercise leads to various noncommunicable diseases. Methodology:A study was conducted at Central Park Housing Society, Lahore using cross sectional study design. Data was collected from 250 residents of Lahore, Pakistan's Central Park Housing Society using the structured tool IPAQ-LF. Structured tool used in this study was applicable on age group between 15-69 years, therefore we included participants aged between 15-69 years in this study. While children, adolescences having age between 10-14 years, adults > 69 years old, pregnant women and those with existing non- communicable diseases were excluded from the study. The Kruskal-Wallis ANOVA test was used to determine whether there was a significant relationship between physical activity and non-communicable diseases. Results: About 20.8% participants had family history of hypertension. Greater physical activity is linked to reduce hypertension risk. Lower physical activity is associated with a higher diabetes risk (18%) compared to the higher activity levels (14%). BMI (p-value=0.00) and random blood sugar level (p-value=0.03) is associated with physical activity. Conclusion: Most of the participants were not involved in moderate physical activity. People who participated in physical activities are at a lower risk of developing diabetes and hypertension. In general, physical activity aids in mitigating harmful chronic diseases.